Inovasi Teknologi dan Penerapannya pada IKM Kota Surakarta, Sebuah Studi Pendahuluan - Setyawan, Anton Agus; Praswati, Aflit Nur Yulia; Nugroho, Sidiq Permono; Isa, Muzakar; Prasetya, Farid Adi; Kurniawan, Fery Indra; Setyawan, M Arkan (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
This study aims to identify the types and levels of technology innovation adopted by Small and Medium Enterprises (SMEs) and cooperatives in Surakarta City, as well as to analyze its impact on their business development. A qualitative approach was applied using surveys, in-depth interviews, and focus group discussions (FGD). The findings indicate that most SMEs have implemented input-level innovations through human resource (HR) training and alternative raw material utilization, but have yet to advance significantly in product development or production process innovation. Business process innovations, especially in digital marketing, have been more widely adopted and directly contributed to increased sales. Key driving factors for innovation include government-provided training programs and revenue growth post-innovation. Meanwhile, obstacles faced by SMEs include limited R&D and training budgets, and inadequate technological auditing capabilities. This study recommends optimizing the roles of local governments and universities in innovation facilitation and providing incentives to support innovation sustainability in the SME sector.